Reviewing RAWP. Is the medical service increment for teaching (SIFT) adequate?. Issue 6604 (17th October 1987) - Bevan, G
Abstract : One issue of interest to the current review of the Resource Allocation Working Party (RAWP) formula is the extra service costs associated with medical teaching. RAWP intended the medical service increment for teaching (SIFT) to cover these costs. Although it is not possible to assess from the methods used to derive the SIFT rate whether it is or is not overgenerous for its intended purpose, the "excellence" elements of teaching hospitals tend to be protected. The financial problems of the teaching hospitals are more likely to be due to the relatively high use of services by local residents. But cutting services of London teaching hospitals to bring this use down to equitable levels may impair their capacity to train medical students.